The IoT Integrated Electric Vehicle Fire Detection System: Case Study of IMEI TEAM UMSIDA - Muhamad Husaini; Sulistiyowati, Indah; Anshory, Izza; Syahrorini, Syamsudduha; Aliffudin, Muchammad (Jurnal Sistem Cerdas, 2024)
Abstract—In the modern era, electric vehicle technology is rapidly developing and emerging as a more environmentally friendly option than fossil fuel vehicles. Despite its many advantages, electric vehicles face safety concerns, especially fire hazards caused by problems with the battery, electrical system, or human error. Fires in electric vehicles can occur due to problems with the lithium-ion battery, accidents, or improper maintenance. Although rare, this risk needs to be considered by following maintenance and safety guidelines. Fire detection systems in electric vehicles are designed to detect and respond to potential fires, provide early warning, and take preventive or emergency action. The system uses NodeMCU esp8266 as the microcontroller, which is connected with a smartphone via WiFi. Data from the MQ2 sensor and the fire sensor are sent and recorded on the IoT platform on the smartphone. This tool is able to detect fires in real-time, but unstable internet or WiFi quality can affect data transmission. Thus, this system is expected to increase safety and reduce the risk of fire in electric vehicles, so that people feel safer and more confident in using this environmentally friendly technology. Keywords— Electric Vehicles; Fie Detector; Monitoring